Targeting Acute Myeloid Leukemia Stem Cells through Perturbation of Mitochondrial Calcium - Anagha Inguva; Mark J. Althoff; Hunter Tolison; Krysta L. Engel; Maria L. Amaya; Anna E. Krug; Tracy N. Young; Mohammad Minhajuddin; Shanshan Pei; Sweta B. Patel; Amanda Winters; Regan Miller; et al. (2024)
Acute myeloid leukemia stem cells (LSCs) are uniquely reliant on oxidative phosphorylation (OXPHOS) for survival. Moreover, maintenance of OXPHOS is dependent on BCL-2, creating a therapeutic opportunity to target LSCs using the BCL-2 inhibitor venetoclax. Although venetoclax-based regimens have shown promising clinical activity, the emergence of drug resistance is prevalent. Thus, in the present study, we investigated how mitochondrial properties may influence venetoclax responsiveness. Our data show that utilization of mitochondrial calcium is fundamentally different between drug-responsive and nonresponsive LSCs. By comparison, venetoclax-resistant LSCs demonstrate an active metabolic (i.e., OXPHOS) status with relatively high levels of calcium. Consequently, we tested genetic and pharmacological approaches to target the mitochondrial calcium uniporter. We demonstrate that inhibition of calcium uptake reduces OXPHOS and leads to eradication of venetoclax-resistant LSCs. These findings demonstrate a central role for calcium signaling in LSCs and provide an avenue for clinical management of venetoclax resistance. Significance: We identify increased utilization of mitochondrial calcium as a distinct metabolic requirement of venetoclax-resistant LSCs and demonstrate the potential of targeting mitochondrial calcium uptake as a therapeutic strategy.